Qualitative Study of the Role of Fathers in Stunting Incidence in South Central Timor Regency - Juni Gressilda Louisa Sine; Regina Maria Boro; Jane A. Peni; Asweros Umbu Zogara (Jurnal Penelitian Pendidikan IPA, 2024)
Stunting is a condition of chronic malnutrition accompanied by disease complications, which has negative impacts, both short and long term. In the short term, children will be at risk and susceptible to infectious diseases, while in the long term, in adulthood they will be at risk of suffering from chronic diseases. Low income affects household nutrition. The incidence of stunting cannot be separated from habits, cultural beliefs, knowledge and perceptions of local communities regarding fulfilling family nutrition. These beliefs have an influence on child care. The aim of this research is to identify the role of fathers in the incidence of stunting in South Central Timor Regency. This type of qualitative research uses focus group discussion (FGD) methods and in-depth interviews. The respondents involved for the qualitative approach were government figures (village heads and sub-district heads), religious leaders, traditional leaders, health services, community health centers and fathers with toddlers totaling 7 people from each village. The results obtained on average are that fathers know the direct causes of stunting, not because of their knowledge but because fathers are less aware of their child's parenting patterns. Parenting patterns regarding monitoring children's meal times, personal hygiene and providing diverse and nutritious food are lacking. On average, a father is busy earning a living, many even work outside the city so their children are entrusted to their grandparents, there is a lack of control in the family so there are many early marriages under the age of 20, the family economy is weak so people have less purchasing power to earn money. nutritious food ingredients. The conclusion from this research is that the role of fathers is one of the causes of stunting in South Central Timor Regency.